KAJIAN LEARNING ORGANIZATION PADA ORGANISASI PUBLIK - Agus Joko Purwanto (LPPM Universitas Terbuka, 2007)
Learning organization can be defined as the ability of organization to advance its capacity creating its future. The concept of learning organization which is common in private sector is also applicable to the public factor. Organization can not learn, only individual that learns. For being a learning organization, organization must facilitate individual with effective structure. At Universitas Terbuka, the Indonesia Open Learning University, individual learning is not related with organizational structure. In some occasion, organizational structure restricted individual learning. At the level of group, organizational structure has been affecting the group abilility for learning. To ovesrcome the inhibition of the formal structure, team usually informal communication channel.